2018
DOI: 10.3389/fonc.2018.00104
|View full text |Cite
|
Sign up to set email alerts
|

Classical NF-κB Metabolically Reprograms Sarcoma Cells Through Regulation of Hexokinase 2

Abstract: BackgroundMetabolic reprogramming has emerged as a cancer hallmark, and one of the well-known cancer-associated metabolic alterations is the increase in the rate of glycolysis. Recent reports have shown that both the classical and alternative signaling pathways of nuclear factor κB (NF-κB) play important roles in controlling the metabolic profiles of normal cells and cancer cells. However, how these signaling pathways affect the metabolism of sarcomas, specifically rhabdomyosarcoma (RMS) and osteosarcoma (OS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 66 publications
0
39
1
1
Order By: Relevance
“…39 HK2 is dominantly regulated by various oncogenic pathways, including c-myc, PI3K/ Akt, NF-κB, and HIF-1α. [40][41][42] Our data showed that suppression of Akt signaling was required for sinomenine inhibited HK2 and glycolysis. Ectopically overexpression of constitutively activated Akt1, Myr-Akt1, partly rescued sinomenineinduced glycolysis inhibition and apoptosis induction.…”
Section: Discussionmentioning
confidence: 67%
“…39 HK2 is dominantly regulated by various oncogenic pathways, including c-myc, PI3K/ Akt, NF-κB, and HIF-1α. [40][41][42] Our data showed that suppression of Akt signaling was required for sinomenine inhibited HK2 and glycolysis. Ectopically overexpression of constitutively activated Akt1, Myr-Akt1, partly rescued sinomenineinduced glycolysis inhibition and apoptosis induction.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, the RNA sequencing data revealed a gene involved in nitrogen metabolism, CPS1, as a potential downstream gene regulated by CARD10. Additionally, the RNA sequencing data revealed several other genes that have been reported to be regulated by the NF‐κB pathway, such as IL6, MAPK1, SSAT, HK2 and GLUT1 . Thus, we hypothesized that CPS1 may also be regulated via the NF‐κB pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, the RNA sequencing data revealed several other genes that have been reported to be regulated by the NF-κB pathway, such as IL6, MAPK1, SSAT, HK2 and GLUT1. [24][25][26][27][28] Thus, we hypothesized that CPS1 may also be regulated via the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NF-κB and MAPK1/2 possess, at least partially, independent roles in TLR9 activation and may be responsible for the metabolic changes seen in CpG-activated MIM −/− B cells. Indeed, NF-κB has been shown to reduce mitochondrial oxidative metabolism in sarcoma cells and MAPK1/2 have been shown to promote glycolytic shift in some cancer types, as well as in rapidly proliferating cells (61,62). This suggests that impaired activation of these modules may underpin the elevated oxidative metabolism in MIM −/− B cells.…”
Section: Discussionmentioning
confidence: 99%